MOLECULAR-WEIGHT AND CONCENTRATION EFFECTS ON GEL SOL TRANSITIONS IN A SEGMENTED RIGID-ROD POLYIMIDE SOLUTION - LEE, SK; CHENG, SZD; WU, ZQ; LEE, CJ; HARRIS, FW; KYU, T; YANG, JC (JOHN WILEY & SONS LTD, 1993)
Gel/sol and order/disorder transitions can be observed in a segmented rigid-rod polyimide solution at different concentrations and molecular weights. This polyimide was synthesized from 3,3',4,4'-biphenyltetracarboxylic dianhydride and 2,2'-bis(trifluoromethyl)-4,4'-diaminobiphenyl in refluxing 3-cresol in a one-step process. Above about 140-degrees-C, the polymers are completely soluble in 3-cresol in a concentration range up to 12(w/w)%. During cooling, the hot solutions undergo a mechanical sol/gel transition to form thermally reversible gels. In the gel state, an ordered structure develops. Both the gel/sol and order/disorder transitions are dependent upon concentration, temperature, and molecular weight, but the two transitions exhibit different kinetics. Possible mechanisms of these transitions are discussed.